Rodent Species Distribution and Hantavirus Seroprevalence in Residential and Forested areas of Sarawak, Malaysia - Nur Elfieyra Syazana Hamdan; Yee Ling Ng; Wei Bin Lee; Cheng Siang Tan; Faisal Ali Anwarali Khan; Yee Ling Chong (Tropical Life Sciences Research, 2017)
Rodents belong to the order Rodentia, which consists of three families in Borneo (i.e., Muridae, Sciuridae and Hystricidae). These include rats, mice, squirrels, and porcupines. They are widespread throughout the world and considered pests that harm humans and livestock. Some rodent species are natural reservoirs of hantaviruses (Family: Bunyaviridae) that can cause zoonotic diseases in humans. Although hantavirus seropositive human sera were reported in Peninsular Malaysia in the early 1980s, information on their infection in rodent species in Malaysia is still lacking. The rodent populations in residential and forested areas in Sarawak were sampled. A total of 108 individuals from 15 species of rodents were collected in residential (n = 44) and forested (n = 64) areas. The species diversity of rodents in forested areas was significantly higher (H = 2.2342) compared to rodents in residential areas (H = 0.64715) (p < 0.001 of Zar-t test based on the Shannon index). Rattus rattus and Sundamys muelleri were present at high frequencies in both localities. An enzyme-linked immunosorbent assay (ELISA) showed that hantavirus-targeting antibodies were absent from 53 tested serum samples. This is the first report of hantavirus seroprevalence surveillance in rodent populations in Sarawak, East Malaysia. The results suggested that hantavirus was not circulating in the studied rodent populations in Sarawak, or it was otherwise at a low prevalence that is below the detection threshold. It is important to remain vigilant because of the zoonotic potential of this virus and its severe disease outcome. Further studies, such as molecular detection of viral genetic materials, are needed to fully assess the risk of hantavirus infection in rodents and humans in this region of Malaysia. Rodent tergolong dalam kumpulan Rodentia yang terdiri daripada tiga Famili di Borneo (Contoh: Muridae, Sciuridae dan Hystricidae). Ini termasuk tikus, tupai dan juga landak. Golongan ini tersebar di serata dunia dan dianggap sebagai haiwan perosak yang mengancam manusia dan haiwan ternakan. Sebahagian spesies rodent adalah sumber pembawa jangkitan Hantavirus (Famili: Bunyaviridae) yang menyebabkan penyakit zoonotik kepada manusia. Walaupun serum manusia pernah dilaporkan seropositif pada Hantavirus di Semenanjung Malaysia pada awal tahun 1980, informasi tentang jangkitan pada spesies rodent di Malaysia masih kekurangan. Populasi rodent di kawasan perumahan dan kawasan hutan di Sarawak telah disampel. Sejumlah 108 individu daripada 15 spesies telah ditangkap di kawasan perumahan (n = 44) dan kawasan hutan (n = 64). Kepelbagaian rodent di kawasan hutan secara signifikan lebih tinggi (H = 2.2342) berbanding rodent di kawasan perumahan (H = 0.64715) (p < 0.001 ujian Zar-t berdasarkan indeks Shannon). Rattus rattus dan Sundamys muelleri amat kerap dijumpai di kedua dua lokaliti. Ujian imunosorben taut-enzim (ELISA) menunjukkan antibodi kursus kepada Hantavirus tidak dapat dikesan daripada 53 sampel serum yang telah diuji. Ini adalah laporan pertama tentang seroprevalensi hantavirus di Sarawak, Malaysia Timur. Hasil kajian menunjukkan bahawa penyebaran Hantavirus tidak berada dalam populasi tikus yang ditangkap di Sarawak, melainkan jika pengesanan di bawah prevalensi rendah iaitu di bawah tahap ambang. Kajian lebih lanjut seperti pengesanan molekul pada komponen viral genetik diperlukan untuk menilai sepenuhnya risiko jangkitan Hantavirus pada rodent dan juga manusia dalam kawasan kajian ini, di Malaysia.